The Influence of Knowledge, Fieldwork Practice and Motivation on Students' Intention in Working at Sharia Banks - Waharani, Sephi; Nurjanah; Ade Fadillah FW Pospos; Nur Kumalahayati (Mabny: Journal of Sharia Management and Business, 2025)
This study aims to analyze the influence of knowledge, fieldwork experience, and motivation on the interest of Islamic banking students at FEBI IAIN Langsa to pursue a career in Islamic banks. The sample used in this study amounted to 100 students. Data analysis was carried out by multiple linear regression. The findings of this study show that simultaneously, knowledge, fieldwork experience, and motivation have a positive and significant influence on students' interest in working in Islamic banks. Partially, knowledge and motivation showed a significant influence on interest in working in Islamic banks, while field work experience did not show a significant influence on the variables of interest.